TO THE STUDY OF ETHNO-CULTURAL SITUATION IN THE MIDDLE INTERFLUVE OF AKSAY AND AKTASH (NORTH DAGESTAN) IN THE I–II MILLENNIA AD - Hapizov, Sahban Magomedovic (History, Archeology and Ethnography of the Caucasus, 2019)
Based on a wide range of various historical sources, the article considers the ethnocultural situation that existed on the territory of the middle course of Aksay and Aktash interfluve for a long historical period of the 1st and the 2nd millennia AD. This region, located on the border of mountains and lowlands remains the contact zone on the territory of which active and diverse ethnocultural, economic and political contacts of cultures and peoples of different origin have been occurring.At an early stage, from the first centuries AD and up to the era of the Great human migration, this was a contact zone between the local (pra-Dagestan) population and the alien Sarmatian-Alan tribes (Sarmatians, Maskuts, Alans). From the 5th – 6th centuries, various Turkic-speaking tribes, such as the Huns-Savirs, Turkuts, then the Khazars, etc. have been taking part in this close ethnic-cultural interaction process. Medieval Dagestan (Avar-)-Turkic contacts in the zone are reflected in the Salatav dialect of the Avar language and in the local toponymy, represented by both Dagestan (Avar) and Turkic toponyms.Archaeological data from the medieval historical sources indicates that until the end of the 14th century the central settlement of this microregion was the large Avar city of Almak. At the very end of the 14th century the famous conqueror Timur Barlas devastated this area during several campaigns. As a result, the population was partially exterminated, and they had to hide in the mountainous Avaria. In the 15th – 17th centuries there was a gradual return of these people to their former places of residence. In 1763, the resettlement of the population from Ingushetia and western Chechnya to this microregion began. It was carried out in the framework of the settlement of the lands of the Endirean princes by the tax-paying population in the territory formerly occupied by the Avar farms. In the 19th – early 20th centuries Chechens settled here en masse. At the very end of 1943, a decision was made to establish the Aukhovsky district, but this process was interrupted by the deportation of Akkins and Chechens to Central Asia at the end of February 1944. As a result, the region that had only existed less than half a year, was liquidated. In the largest part of its territory in 1944, the Novolaksky district was founded. In the late 1950s’ Chechens and Akkins returned to Dagestan. At the turn of the 80s’ – 90s’ interethnic relations in the area have deteriorated. The situation escalated in the 90s’ after the decision was made to restore the Aukhovsky district without taking into account the opinion of a significant part of the population. This uncertainty remains to this day, since no final decision has been made on the status of this region.
Keywords: Novolaksky district; Kazbekovsky district; Aukhovsky district; Avars; Laks; Akkins; Chechens.